Sustainable agriculture - Mason, John, 1951- (Landlinks Press, 2003)
This book is about foreseeing and understanding the problems associated with the technological revolution in farming practices, and explains the concepts and long-term benefits of sustainable farming systems.
Keywords: Sustainable agriculture.; Sustainable development.; Agriculture durable.; Développement durable.; sustainable development.; sustainable agriculture (discipline); TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science.; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General.; Sustainable agriculture; Sustainable development; Nachhaltigkeit; Biologische Landwirtschaft; Landwirtschaft; Agricultura sustentável.; Permaculture.